Política de regularização fundiária em Rondônia: limitações do programa terra legal e expectativas socioterritoriais - Alyson Fernando Alves Ribeiro; Ricardo Gilson da Costa Silva; Josefa de Lisboa Santos (Confins)
Terra Legal Amazonia its a Program that seeks to solve the problem of legal security of federal lands, regulating Brazilian state areas measuring up to 15 fiscal modules occupied by squatters in the nine states of the Legal Amazon. The presenting text analyzes the development of the program in the Amazon region, with special attention to its execution in the state of Rondônia, from year 2009 to 2014. The results from regularized possessions through the issuance of domain titles, indicate structural limitations in managing the program, what impacts  the proposed goals and demonstrates the fragility of one of the main public policies affecting large portions of the rural properties on Rondônia state. At last, it is understood that rural properties insecurity in terms of the law, especially for small farmers, tends to delay the resolution of the land tenure chaos as a structural problem in the agrarian space of Rondônia.